Counter Terrorism Prediction and Risk Evaluation (C-TRIP) - Yash Shirsath; Vedant Bhosale; Manoj Deshpande; Shilpali Bansu (International Journal of Information Security Engineering, 2024)
The global landscape in the 21st century is marked by complex and evolving security challenges, none more pressing than the threat of terrorism. Acts of terror have left a profound impact on societies, economies, and governments worldwide, underscoring the critical importance of effective counter terrorism strategies. The “Counter Terrorism Prediction and Risk Evaluation (C-TRIP)” represents a significant stride in addressing this ever-pressing challenge. In a time marked by global security challenges, “Counter Terrorism Prediction and Risk Evaluation (C-TRIP)” is emerging as an innovative solution to deal with the ever-evolving terrorist threats. The project arises from the pressing need for predictive systems. It can anticipate and mitigate the possibility of terrorism. The motivation is external This effort is reflected in the rise and proliferation of terrorist incidents dramatically in recent years. Traditional counter terrorism response strategies are not the right length of time. Timely, data-driven interventions are needed to address this matter of great importance. This offers an extensive overview of current literature. Critically examines the strengths and limitations of past research. Define what is important is the research gap in the current work, and the search for a new framework was emphasized which can provide an accurate risk assessment and early warning. It employs a data-driven methodology utilizing machine learning and data analysis techniques to predict and assess terrorist incidents. C-TRIP aims to enhance decision-making in counter terrorism efforts by providing timely and accurate insights into the likelihood and severity of potential terrorist events.
Keywords: Architecture; Counterterrorism; data-driven interventions; decision-making; early warning; experimental results; global landscape; global security; methodology; predictive systems; security challenges; terrorism; threat assessment